2013
DOI: 10.3389/fpls.2013.00121
|View full text |Cite
|
Sign up to set email alerts
|

KNOX1 genes regulate lignin deposition and composition in monocots and dicots

Abstract: Plant secondary cell walls are deposited mostly in vascular tissues such as xylem vessels, tracheids, and fibers. These cell walls are composed of a complex matrix of compounds including cellulose, hemicellulose, and lignin. Lignin functions primarily to maintain the structural and mechanical integrity of both the transport vessel and the entire plant itself. Since lignin has been identified as a major source of biomass for biofuels, regulation of secondary cell wall biosynthesis has been a topic of much recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 63 publications
5
28
0
Order By: Relevance
“…Mutations on CAD2 also caused easy shattering, further demonstrating that lignin plays an important role in that phenomenon. Our results are consistent with a previous report that overexpression of a KNOX gene in maize and tobacco (Nicotiana tabacum) reduces lignin concentrations by inhibiting at least two steps in that biosynthesis pathway (Townsley et al, 2013).…”
Section: The Osh15-sh5 Dimer Functions In Lignin Biosynthesissupporting
confidence: 93%
“…Mutations on CAD2 also caused easy shattering, further demonstrating that lignin plays an important role in that phenomenon. Our results are consistent with a previous report that overexpression of a KNOX gene in maize and tobacco (Nicotiana tabacum) reduces lignin concentrations by inhibiting at least two steps in that biosynthesis pathway (Townsley et al, 2013).…”
Section: The Osh15-sh5 Dimer Functions In Lignin Biosynthesissupporting
confidence: 93%
“…Thus, class I KNOX genes lower GA levels and activate CK accumulation. In addition, it was also reported that KNOX genes repress the biosynthesis of lignin, a major secondary cell wall component in Arabidopsis and maize [33,34] (Figure 2). …”
Section: Knox Downstream Pathwaysmentioning
confidence: 85%
“…The expression pattern of CCOMT and CAD indicated that lignin biosynthesis was reduced during the early stage of SR development. In addition, upregulation of KNOX1 in I-stage and S-stage was negatively correlated with the expression of lignin biosynthesis key genes (CCOMT and CAD) (Guo et al 2001;Townsley et al 2013) suggesting that reduction of lignin biosynthesis corresponds to SR development (Firon et al 2013;Testone et al 2012).…”
Section: Functional Analysis Of Significant Genes During Phase Transimentioning
confidence: 99%